Mechanism of basic calcium phosphate crystal-stimulated matrix metalloproteinase-13 expression by osteoarthritic synovial fibroblasts: inhibition by prostaglandin E2. Issue 12 (26th January 2008) - Molloy, E S; Morgan, M P; Doherty, G A; McDonnell, B; O'Byrne, J; Fitzgerald, D J; McCarthy, G M
Abstract : Objective: To determine the mechanism of matrix metalloproteinase (MMP)-13 upregulation in osteoarthritic synovial fibroblasts (OASF) in response to stimulation with basic calcium phosphate (BCP) crystals and to investigate the effect of prostaglandin (PG)E2 on BCP crystal-stimulated MMP expression. Methods: Primary OASF were stimulated with BCP crystals; mRNA expression was measured by real-time reverse transcription–polymerase chain reaction and protein levels were assessed by Western blotting. Results: BCP crystals upregulated MMP-13 mRNA expression over 20-fold and increased MMP-13 protein production in OASF. BCP crystal-stimulated MMP-13 mRNA expression was blocked by inhibition of the extracellular regulated kinase (ERK1/2) and p38 mitogen activated protein kinase (MAPK) pathways and inhibition of the activation of nuclear factor κB. Addition of exogenous PGE2 downregulated BCP crystal-stimulated MMP-13 expression. In contrast, PGE2 upregulated, and had no effect, on BCP crystal stimulated MMP-3 and MMP-1 mRNA expression, respectively. These effects of PGE2 were diminished by L-161, 982, a selective EP4 receptor antagonist, and mimicked by CAY10399, a selective EP2 receptor agonist, and forskolin, an adenylate cyclase activator. Conclusions: These data suggest that BCP crystal induction of MMP-13 expression may involve the ERK1/2 and p38 MAPK pathways and activation of nuclear factor κB; this upregulation of MMP-13 may contribute to the accelerated cartilage breakdown in BCP crystal-associated osteoarthritis. PGE2 had contrasting effects on BCP crystal-stimulated MMP-3 and MMP-13 mRNA expression, mediated in an EP2/EP4/cAMP-dependent manner, suggesting that PGE2 may have beneficial as well as deleterious effects in BCP crystal-associated osteoarthritis.